Movimentos sociais estudantis no Brasil em fins de 2016: Uma análise das ocupações escolares em Ituiutaba - MG - Marques, Eduardo Henrique de Freitas (2019)
The present study is a result of the Master Degree on the Education Research Program of the Federal University of Uberlândia, linked to the research line "Work, Society and Education" and seeks to present and analyze aspects that involve students’ occupations that occurred in Brazil at the end of 2016. We seek to present questions that involve the current youth present in the public High School system in Brazil and, shortly after we developed an analysis of the occupations that occurred in the state of São Paulo in 2015, against the closure of schools and the relocation of students, an event that served as the basis and inspiration for the occupation movements that occurred in Brazil later. Based on these questions, we discussed the occupations in Brazil and then focused our dissertation in the city of Ituiutaba - Minas Gerais, where two, out of the four existing High Schools \in the city, took part in the occupation process, representing a significant half percentage. After the presentation of the city and the two schools, we observed two virtual pages, linked to the social network Facebook, which were created specifically to publicize, propagate and report the events that occurred in the daily routine of the occupations. Finally, we present interviews with four participants of the occupations in Ituiutaba - Minas Gerais, seeking to report their opinions and experiences they had in the two occupied schools. Thus, we hope to contribute to research involving issues related to youth, school occupations, and ways of student organization and reports of experience with occupation movements.